2021
DOI: 10.1136/bmjopen-2021-050341
|View full text |Cite
|
Sign up to set email alerts
|

‘Slash and clear’ vector control for onchocerciasis elimination and epilepsy prevention: a protocol of a cluster randomised trial in Cameroonian villages

Abstract: IntroductionOnchocerciasis, caused by the filarial nematode Onchocerca volvulus, remains endemic in Cameroon despite decades of community-directed treatment with ivermectin (CDTI). CDTI is often hampered by coendemicity with loiasis (another filariasis caused by Loa loa) in some areas. Strong epidemiological evidence suggests that O. volvulus infection increases the risk for onchocerciasis-associated epilepsy (OAE) among Cameroonian children. This highlights the urgent need to strengthen onchocerciasis elimina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…In a formerly highly endemic area in the Mbam and Sanaga river valleys of Cameroon, Siewe Fodjo et al [40] found an Ov16 seropositivity of 47% (68/145) in Bilomo (Centre Region) and 52% (13/25) in Kelleng (Littoral Region) among children aged 7–10 years after >13 years of CDTI. A factor likely involved in the persistence of onchocerciasis in this area is the very high (and perennial) biting rates of the blackfly vectors, as documented in other localities of the Mbam and Sanaga river systems, both historically and recently [41,42]. As our study area was originally mesoendemic, and annual biting rates in the region were of the order of 3,000–4,000 per person [19], it would be advisable to update entomological studies in the Tain District and Wenchi Municipality of Ghana to better understand the potential contribution of blackfly abundance, species composition and transmission intensity to persistent infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a formerly highly endemic area in the Mbam and Sanaga river valleys of Cameroon, Siewe Fodjo et al [40] found an Ov16 seropositivity of 47% (68/145) in Bilomo (Centre Region) and 52% (13/25) in Kelleng (Littoral Region) among children aged 7–10 years after >13 years of CDTI. A factor likely involved in the persistence of onchocerciasis in this area is the very high (and perennial) biting rates of the blackfly vectors, as documented in other localities of the Mbam and Sanaga river systems, both historically and recently [41,42]. As our study area was originally mesoendemic, and annual biting rates in the region were of the order of 3,000–4,000 per person [19], it would be advisable to update entomological studies in the Tain District and Wenchi Municipality of Ghana to better understand the potential contribution of blackfly abundance, species composition and transmission intensity to persistent infection.…”
Section: Discussionmentioning
confidence: 99%
“…Entomological studies should also be undertaken in the study area to assess infection levels in simuliid population samples. [41,42]. As our study area was originally mesoendemic, and annual biting rates in the region were of the order of 3,000-4,000 per person [19], it would be advisable to update entomological studies in the Tain District and Wenchi Municipality of Ghana to better understand the potential contribution of blackfly abundance, species composition and transmission intensity to persistent infection.…”
Section: Discussionmentioning
confidence: 99%
“…Our research team has been conducting a research project for the past three years, aiming to implement the “Slash and Clear” approach along segments of the longest river in Cameroon, the Sanaga River, and investigate community perceptions as well as the sustainability of this intervention [ 23 ]. Thus, the first phases of the project consisted of formative research, whereby qualitative studies were conducted to understand how the community experienced the blackfly nuisance and whether the “Slash and Clear” intervention was welcomed in the study villages.…”
Section: Introductionmentioning
confidence: 99%
“…Although the Sanaga river (the longest river in Cameroon) also harbors several blackfly breeding sites which render the surrounding villages endemic for onchocerciasis as well as OAE [ 23 ], few studies have been done in villages along its banks. In a bid to identify breeding sites in the Sanaga river where vector control activities can be implemented to reduce onchocerciasis transmission and epilepsy prevalence/incidence, we initiated a project in selected villages along this river [ 24 ]. In the present paper, we report the baseline findings regarding the epilepsy situation in the study villages and how this relates to the onchocerciasis endemicity levels prior to implementing vector control measures.…”
Section: Introductionmentioning
confidence: 99%